A method to assess safety and comfort for different ships types in a region of interest. (15th April 2022) - Gaggero, Tomaso; Bucciarelli, Filippo; Besio, Giovanni; Mazzino, Andrea; Villa, Diego
Abstract: The worldwide increase in ship traffic poses a series of challenges for the designer, the crew and the authorities involved in ship traffic management. Depending on the ship type, both onboard comfort and safety represent two key aspects to be taken into account during the ship life. In the present paper, the focus is on the assessment of the safety and comfort in service during navigation in real weather conditions by focusing on an entire route instead of on a single ship. A method for assessing the safety and comfort levels of specific routes is presented and discussed in the paper. In particular, a statistical approach to set up limit thresholds able to quantify the level of navigation safety and comfort for different ship types in a specific area is presented based on historical weather data. The method is based on the Automatic Identification System (AIS) data for the traffic characterization, a strip theory for the seakeeping calculations and historical meteorological data for the environment definition for a specific area in the Mediterranean Sea. Highlights: Definition of the statistical range of safety and comfort indexes for ships in the Mediterranean sea area. Use of the AIS and weather data in the Pelagos area to extract real safety navigation indexes. Definition of a robust and reliable procedure to define safety and comfort indexes for ships in a sea region.